Ways of settling a judo fight at consecutive stages of sports competitions - Adam, M.; Wolska, B.; Tabakov, S. (Baltic Journal of Health and Physical Activity, 2018)
Background: At successive stages of sports competition, judo contestants aim at achieving the best sports result. Each fight can be resolved by an effectively executed attack before the regular time (ippon or double waza-ari) or by a better score for efficient attacks (waza-ari or yuko). The victory can also be achieved for penalties awarded to the opponent (shido) or when he/she is disqualified for infractions of the sports rules of the International Judo Federation.